THE PROCESS OF PROVING FRAUDULENT ACTIONS IN THE FIELD OF BANK LENDING (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article analyzes the main directions on the facts of fraudulent actions in the field of lending with a list of possible actions aimed at the initial collection of evidence. Separate issues of proof for the category of crimes under consideration are considered by listing the circumstances, the totality of which can confirm the existence of intent to commit a crime. A list of investigative actions carried out at the initial stage of the investigation is proposed.